Amelioration of aorta morphology in a spontaneous hypertensive rat (shr) by Syzygium polyanthum - Ismail, Azlini; Wan Ahmad, Wan Amir Nizam; Baharun, Bibi Nur Bazlini; Ramli, Nurul Syahida; Noordin, Liza (2018)
Background: Prolonged uncontrolled hypertension can lead to vessels damage; manifested as abnormal morphology changes. Sygyzium polyanthum has been shown to has blood pressure lowering effects in SHR rats.